Single-bite versus double-bite technique for mapping biopsies during endoscopic surveillance for hereditary diffuse gastric cancer: a single-center, randomized trial - Pappas, Apostolos; Tan, Wei Keith; Waldock, William; Richardson, Susan; Tripathi, Monika; Januszewicz, Wladyslaw; Roberts, Geoffrey; O'Donovan, Maria; Fitzgerald, Rebecca C.; di Pietro, Massimiliano (Endoscopy, 2020)
Background Endoscopic surveillance is recommended in patients with hereditary diffuse gastric cancer (HDGC) who refuse or want to delay surgery. Because early signet-ring cell carcinoma (SRCC) can be inconspicuous, the current surveillance endoscopy protocol entails 30 random biopsies, which are time-consuming. This study aimed to compare single-bite and double-bite techniques in HDGC surveillance. Methods Between October 2017 and December 2018, consecutive patients referred for HDGC surveillance were prospectively randomized to the single- or double-bite arm. The primary outcome was the diagnostic yield for SRCC foci. Secondary outcomes were: procedural time for random biopsies; comfort score; biopsy size; and quality of specimens, the latter assessed by the presence of muscularis mucosa, crush artifact, and proportion usable for diagnostic assessment. Results 25 patients were randomized to the single-bite arm and 23 to the double-bite arm. SRCC foci were detected in three and four patients in the single- and double-bite arms, respectively (P = 0.70). The procedural time for the double-bite arm (12 minutes, interquartile range [IQR] 4) was significantly shorter than for the single-bite arm (15 minute, IQR 6; P = 0.01), but comfort scores were similar. The size of the biopsies in the double-bite arm was significantly smaller than in single-bite arm (2.5 mm vs. 3.0 mm; P < 0.001) but this did not affect the presence of muscularis mucosa (P = 0.73), artifact level (P = 0.11), and diagnostic utility (P = 0.051). Conclusion For patients undergoing HDGC surveillance, the double-bite technique is significantly faster than the single-bite technique. The diagnostic yield for SRCC and the biopsy quality were similar across both groups.